(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The article presents the materials of research work based on the database of modern foreign and domestic literature on hysterectomy. The data on total hysterectomy in recent years were studied, the indications for hysterectomy and the course of the postoperative period were analyzed, the frequency of occurrence of complications and their structure were clarified. As a result of the study, predictors and the most frequent pathological processes were identified.